FIGUR IBU PADA CERPEN â€œREMBULAN DI MATA IBUâ€ KARYA ASMA NADIA: The Mother Figure in The Short Story â€œRembulan di Mata Ibuâ€ by Asma Nadia - Achril Zalmansyah; Yoga Irawan; Annisa Fitriani (Kantor Bahasa Provinsi Maluku, 2023)
Abstract The mother figure has always been an inspiration in writing literary works in Indonesia. One is the short story